ANALISIS ENERGI BIOMASSA DENGAN GENERATOR TERMOELEKTRIK (TEG) UNTUK MESIN PENCACAH SAMPAH ORGANIK - Ralfy Nathan Gibran, (2021)
Biomass is a renewable and sustainable energy source, where the energy source comes from organic waste such as agricultural, forestry, factory, and household waste. One of the wastes from forestry production is wood. The waste produced is the remaining wood from cutting, it can be in the form of powder, cut wood, and others. Wood can be converted into a product called wood pellets that can replace the performance of coal fuel. Most chopping machines sold in the market for the public also still use gasoline as an energy source to drive the motor of the cutting blade. So, this research was conducted to create an alternative energy source that can meet the needs of electrical energy on a small scale, using a thermoelectric generator (TEG). This study aims to determine the performance of wood pellets and a thermoelectric generator as an energy source for the organic waste chopper and the amount of power that can be generated. From the results of the study, it can be concluded that the organic waste chopper cannot work because the power generated by the thermoelectric generator is not enough, which is 0.0447 Watt. The cooling system with ice cubes causes an electrical short because the ice cubes melt and the water drips onto the wires of the thermoelectric generator.